DETERMINATION OF TOTAL PHENOLIC, ANTIOXIDANT, CHLOROPHYLL AND CAROTENOID AMOUNTS OF Lavandula angustifolia (LAVENDER) AND Salvia rosmarinus (ROSEMARY) UNDER HEAVY METAL (Cu2+, Cd2+) STRESS - Buran, Abayhan; Durğun, Murat Ersin; Karaman, Erhan (Bartin University, 2022)
In this study, Total Phenolic, Antioxidant, Chlorophyll and Carotenoid amounts of Lavandula angustifolia and Salvia rosmarinus plants subjected to heavy metal stress were determined. Copper and cadmium were used as heavy metals. A decrease in total chlorophyll (Cl), chlorophyll-a (Cl-a), chlorophyll-b (Cl-b) and carotenoid amounts was observed for both plants. It was observed that there was an increase in the amount of total antioxidant and total phenolic substance. According to the results of S. rosmarinus for the amount of phenolic substances, 81.70±1.68 mg/g GAE for the control group; 84.60±2.09 mg/g GAE for the heavy metal group. According to the antioxidant substance content results, 3.92±0.08 mmol/g TEAC for the control group; 4.02±0.01 mmol/g TEAC for the heavy metal group. According to the results for L. angustifolia for phenolic amounts, 80.05±2.25 mg/g GAE for the control group; 88.65±2.52 mg/g GAE for the heavy metal group. According to the antioxidant substance content results, 3.91±0.01 mmol/g TEAC for the control group; It was obtained as 3.99±0.01 mmol/g TEAC for the heavy metal group. Total Cl amount was determined 1.71±0.03 mg/g for S. rosmarinus control group, 1.04±0.02 mg/g for heavy metal group. Cl-a amount was 0.42±0.02 mg/g for the control group, 0.25±0.02 mg/g for the heavy metal group. Cl-b amount was 0.69±0.02 mg/g for the control group, 0.35±0.01 mg/g for the heavy metal group. The total amount of carotenoids was determined as 0.24±0.01 mg/g for the control group and 0.20±0.01 mg/g for the heavy metal group. Total Cl amount was 0.80±0.02 mg/g for L. angustifolia control group, 0.68±0.03 mg/g for heavy metal group. The amount of Cl-a was 0.25±0.01 mg/g for the control group, 0.22±0.01 mg/g for the heavy metal group. The amount of Cl-b was 0.30±0.01 mg/g for the control group, 0.29±0.01 mg/g for the heavy metal group. Total carotenoid amount was determined as 0.14±0.02 mg/g for the control group and 0.11±0.01 mg/g for the heavy metal group. As a result of the analyzes, the total phenolic, total antioxidant, total chlorophyll and carotenoid amounts of rosemary and lavender plants were determined. SEM images were examined to observe whether the heavy metal application in the study caused changes on the plant leaves. It was observed that there was a decrease in the amounts of chlorophyll and carotenoids, and an increase in the amounts of antioxidants and phenolic substances.

Bu çalışmada, ağır metal stresi uygulanan Lavandula angustifolia (Lavanta) ve Salvia rosmarinus (Biberiye) bitkilerinin Toplam Fenolik, Antioksidan, Klorofil ve Karotenoid miktarları belirlenmiştir. Ağır metal olarak bakır (II) ve kadmiyum (II) kullanılmıştır. Çalışmadan elde edilen sonuçlara göre, ağır metal stresi uygulanan grupta toplam karotenoid miktarında bir düşüş yaşanmıştır. Kontrol grubu kıyas alınarak ağır metal grubuna ait sonuçlara bakıldığında, her iki bitki için toplam klorofil, klorofil-a ve klorofil-b miktarlarında bir azalma gözlemlenmiştir. Yapılan analizler ve ölçümler sonucunda 1 mM bakır çözeltisi ve 100 µM kadmiyum çözeltisi ile ağır metal stresi uygulanan bitkilerin etanol, metanol ve su çözücüleri için toplam fenolik, toplam antioksidan, toplam klorofil ve karotenoid miktarları belirlenmiştir. Ağır metal ve kontrol gruplarına uygulanan analizlerle birlikte ağır metal stresi uygulanan bitkiler ve kontrol grubundaki bitkiler için gözlemlenen farklılıklar ortaya konmuştur. Ağır metal uygulanan grupta, kontrol grubuna kıyasla, toplam antioksidan madde ve toplam flavonoid madde miktarında bir miktar artış gözlemlenmiştir. Çalışmadaki ağır metal uygulamasının, bitki yaprakları üzerindeki değişikliklere sebep olup olmadığını gözlemlemek için SEM görüntüleri incelenmiştir. Sonuç olarak ağır metal stresinde antioksidan ve fenolik madde miktarının arttığı, toplam klorofil ve toplam karotenoid miktarının ise azaldığı gözlenmiştir.
AĞIR METAL (Cu2+, Cd2+) STRESİ UYGULANAN Lavandula angustifolia (LAVANTA) VE Salvia rosmarinus (BİBERİYE) BİTKİLERİNİN TOPLAM FENOLİK, ANTİOKSİDAN, KLOROFİL VE KAROTENOİD MİKTARININ BELİRLENMESİ
Keywords: Structural Biology; Yapısal Biyoloji; Food Engineering; Gıda Mühendisliği